A inclusão dos estudantes com deficiência no Centro de Formação de Professores da Universidade Federal de Campina Grande : desafios e possibilidades - Dantas, Nozângela Maria Rolim (2017)
Public policies for Higher Education aimed at people with disabilities have given access to this population to the higher Education. In this sense, this study aimed to understand the impact of national policies to guarantee the access and permanence of students with disabilities at the Federal University of Campina Grande (UFCG), within the framework of the Teacher Training Center (CFP), in the city of Cajazeiras (PB). From this objective, we sought to identify and analyze the actions adopted by the institution in order to guarantee the access and the permanence of students with disabilities from the perspective of management, teachers and the student with the disability. For this purpose, a qualitative field research was conducted in the form of a Case Study. For data collection, semi-structured interviews were used with 14 subjects including: four managers, five professors and five students. Also four documents of the institution were analyzed: the Institutional Development Plan (PDI), the Statute of the UFCG, the General Regulation of Undergraduate Education and the General Rules. In order to ascertain the conjuncture of researches at the national level, a bibliographical research was carried out based on the principles of the Knowledge State, on the thesis banks of CAPES and the BDTD. The data were analyzed according to Laurence Bardin's Content Analysis principles using the NVIVO 11 software. The results of the interview analysis were organized into three categories, each with two subcategories: Policies (National and Institutional Policies), Actions of Inclusion (Access and Permanence) and Teaching Performance (Pedagogical Practices and Teacher Training). As a result of this research, it was observed that the CFP and the UFCG, as an institution, have sought to develop actions that can assist the student with disabilities, but these are still punctual, not covering national inclusion policies in their entirety. In addition, it can be seen that the institution is not yet ready to receive students with disabilities in their academic space, because, as it does not yet have an institutional policy focused on inclusive education, their initiatives are still timid: the actions developed for the promotion the access and permanence of this student are isolated, depending, in most cases, on the initiative of some professors and employees. Therefore, it is expected that the present study may serve as a subsidy for the development of institutional inclusion policies for the UFCG, as well as support for other research and more effective institutional actions, which will help in the development of an inclusive university culture.